PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Ramadhani Fitri; Sari Andini (MES: Journal of Mathematics Education and Science, 2018)
Abstract. This research was conducted based on the lowed capacity draf knowled matematic the student in junior high school one Pasir Penyu. The purpose this research was to obtain draf knowled matematic the student of useing learning model problem solving. The research desain of use randomied subjects Posttest Only Control Group Desin. Data analisis technique in testing used t-tes. The results of analysis was gotteh thet tcount = 2,950 and ttable = 2,0003. So the conclusied is “The capacity draf knowled matematic the student with of using learning model problem solving be better. From of The capacity draf knowled matematic the student. With of using knvensional at class VIII junior High School One Pasir Penyu. Keywords: problem solving, understanding of mathematical concept